Fellow creatures : our obligations to the other animals - Korsgaard, Christine M (Uehiro Series in Practical Ethics, 2018)
This book argues that we are obligated to treat all sentient animals as “ends in themselves.” Drawing on a theory of the good derived from Aristotle, it offers an explanation of why animals are the sorts of beings who have a good. Drawing on a revised version of Kant’s argument for the value of humanity, it argues that rationality commits us to claiming the standing of ends in ourselves in two senses. As autonomous beings, we claim to be ends in ourselves when we claim the standing to make laws for ourselves and each other. As beings who have a good, we also claim to be ends in ourselves when we take the things that are good for us to be good absolutely and so worthy of pursuit. The first claim commits us to joining with other autonomous beings in relations of reciprocal moral lawmaking. The second claim commits us to treating the good of every sentient animal as something of absolute importance. The book also argues that human beings are not more important than, superior to, or better off than the other animals. It criticizes the “marginal cases” argument and advances a view of moral standing as attaching to the atemporal subjects of lives. It offers a non-utilitarian account of the relationship between the good and pleasure, and addresses questions about the badness of extinction and about whether we have the right to eat animals, experiment on them, make them work for us, and keep them as pets.